A new inverse problem for the diffusion operator - Koyunbakan, Hikmet (Pergamon-Elsevier Science Ltd, 2006)
In this work, we have estimated nodal points and nodal lengths for the diffusion operator. Furthermore, by using these new spectral parameters, we have shown that the potential function of the diffusion operator can be established uniquely. An analogous inverse problem was solved for the Sturm-Liouville problem in recent years. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: diffusion operator; nodal point